PENINGKATAN KETERAMPILAN FISIK MOTORIK MELALUI NYANYIAN DAN GERAKAN DALAM BERWUDHU PADA ANAK USIA DINI - Novi Ade Suryani (Journal Of Dehasen Educational Review, 2020)
This study aims to determine the Physical Motor Skills through singing and movement in Ablution in Children 5-6 years (Group B) in PAUD Insan Cita of Bengkulu City. This type of research is Classroom Action Research. The design in this study uses two cycles namely, Cycle I and Cycle II where in each cycle consists of two meetings. Each cycle consists of planning, implementing, observing and reflecting. From the data analysis that has been done, the results of the study show that the implementation of learning to improve ablution skills in early age group B can be categorized as "very good" at 3.95. Children's success rate in learning to improve ablution skills in learning is categorized as "developing as expected" because it has an average of 92%.